A Tale of Two Sitters : Adventures of Wishbone #9 - Barkan, Joanne; Dickens, Charles, 1812-1870. (Milwaukee, WI : Gareth Stevens Pub., 1999)
When David enlists Joe's aid in babysitting, Wishbone escapes from his noisy home and imagines himself as Charles Darnay, a young Frenchman who, despite great danger, returns to France during the Revolution to help a friend.
Originally published: Allen, Tex. : Big Red Chair Books, c1998. (The adventures of Wishbone ; #9)
Keywords: Dogs -- Fiction; Friendship -- Fiction; France -- History -- Revolution, 1789-1799 -- Fiction